A Study To Assess Desarda Vs Lichtenstein Technique For The Treatment Of Primary Inguinal Hernia (Journal of Pharmaceutical Negative Results, 2022)
Background: The present study was conducted for assessing and comparing the efficacy of Desarda vs Lichtenstein technique for thetreatment of primary inguinal hernia.Materials & Methods: 100 patients scheduled to undergo treatment for inguinal hernia were enrolled. Complete demographic andclinical details of all the patients was obtained. All the patients were randomized into two study groups: Group A (50 patients)-undergoing treatment by Desarda technique, and Group B (50 patients)- undergoing treatment by Lichtenstein technique. Forperforming Lichtenstein tension-free mesh repair, a polypropylene mesh was trimmed to fit the inguinal floor. Chronic pain wasassessed on a VAS score of 0 to 10 with 7 to 10 indicating strong pain while 3 to 6 indicating moderate pain. All the results weresubjected to statistical analysis using SPSS software.Results: Group A and group B subjects took 15.3 days and 14.2 days respectively for returning to basic activity. Group A and groupB subjects took 5.1 days and 8.3 days respectively for returning to home activity (p- value < 0.05). Mean hospital stay was 3.2 daysand 2.9 days among subjects of group A and group B respectively. Foreign body sensation was felt in one patient each of both thestudy groups. Incidence of seroma formation was higher among the patients of group B in comparison to patients of group A. Meanoperative time was significantly lower among patients of group A.Conclusion: Outcome is better for Desarda technique in comparison to Lichtenstein technique for the treatment of primary inguinalhernia.